Genome-wide characterization and expression analysis of MYB transcription factors in Gossypium hirsutum. Issue 1 (December 2016) - Salih, Haron; Gong, Wenfang; He, Shoupu; Sun, Gaofei; Sun, Junling; Du, Xiongming
Abstract Background MYB family proteins are one of the most abundant transcription factors in the cotton plant and play diverse roles in cotton growth and evolution. Previously, few studies have been conducted in upland cotton, Gossypium hirsutum . The recent release of theG. hirsutum genome sequence provides a great opportunity to identify and characterize the entire upland cotton MYB protein family. Results In this study, we undertook a comprehensive genome-wide characterization and expression analysis of the MYB transcription factor family during cotton fiber development. A total of 524 non-redundant cotton MYB genes, among 1986 MYB and MYB-related putative proteins, were identified and classified into four subfamilies including 1R-MYB, 2R-MYB, 3R-MYB, and 4R-MYB. Based on phylogenetic tree analysis, MYB transcription factors were divided into 16 subgroups. The results showed that the majority (69.1 %) ofGhMYBs genes belong to the 2R-MYB subfamily in upland cotton. Conclusion Our comparative genomics analysis has provided novel insights into the roles of MYB transcription factors in cotton fiber development. These results provide the basis for a greater understanding of MYB regulatory networks and to develop new approaches to improve cotton fiber development.